2021
DOI: 10.3389/fphar.2021.693796
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency of Hydroxychloroquine for the Treatment of Primary Sjögren’s Syndrome: A Systematic Review and Meta-Analysis

Abstract: Objectives: This meta-analysis was conducted to evaluate the effects of hydroxychloroquine (HCQ) in the treatment of primary Sjögren’s syndrome (pSS).Methods: Nine databases were searched for data collection. We used clinical features, including involvement in superficial tissues and visceral systems, and experimental findings, including Schirmer’s test, unstimulated salivary flow rate (uSFR), C-reactive protein (CRP), erythrocyte sedimentation rate (ESR) and immunoglobulins (IgG, IgM and IgA) as major outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 29 publications
1
13
0
3
Order By: Relevance
“…Regular physical exercise (endurance training) may prove beneficial. Hydroxychloroquine has been mentioned in reviews as a possible treatment option for fatigue, but there is currently no evidence of statistically significant improvement [126].…”
Section: Systemic Symptomsmentioning
confidence: 99%
“…Regular physical exercise (endurance training) may prove beneficial. Hydroxychloroquine has been mentioned in reviews as a possible treatment option for fatigue, but there is currently no evidence of statistically significant improvement [126].…”
Section: Systemic Symptomsmentioning
confidence: 99%
“…Hydroxychloroquin wird in Übersichtsarbeiten als mögliche Therapie der Fatigue angeführt. Bisher konnte jedoch nicht nachgewiesen werden, dass es zu statistisch signifikanter Besserung führt [126].…”
Section: Systemische Symptomeunclassified
“…Hydroxychloroquin wird in Übersichtsarbeiten als mögliche Therapie der Fatigue angeführt. Bisher konnte jedoch nicht nachgewiesen werden, dass es zu statistisch signifikanter Besserung führt[126].Eine rezente multizentrische klinische Studie mit Hydroxychloroquin zeigte eine Reduktion des AV-Block-Rezidivs um mehr als die Hälfte (von 18 % auf 7,4 %)[131]. Daher kann die Einnahme von Hydroxychloroquin während der Schwangerschaft von Ro/SS-A Antikörper-positiven Müttern zur Prophylaxe eines fetalen AV-Blocks erwogen werden.…”
unclassified
“…The efficacy of hydroxychloroquine in SSDE has not been established. A 2021 systematic review and meta-analysis showed improvement in xerostomia, but did not show significant relief of ocular or other systemic symptoms [ 28 ]. Common side effects include retinal toxicity, with a risk of cardiac, gastrointestinal, dermatological, and neuromuscular adverse effects [ 29 ].…”
Section: Conventional Treatmentsmentioning
confidence: 99%